Gestão da cadeia de suprimentos na indústria citrícola: uma proposta de modelo de planejamento integrado utilizando dinâmica de sistemas - Ferreira, José Orlando (2014)
Suitable coordination systems are crucial to the sustained competitiveness of agribusiness systems. Nevertheless, some agribusiness systems have serious deficiencies in their integrated planning, generating with negative disputes between the members in the chain, which can lead in many cases to the loss of competitiveness. The orange agribusiness system, which has a significant importance as a currency generator and employment, not only in Brazil but also in many other countries, has faced serious problems of competitiveness. Disease threats, particularly, with the "greening" as the most critical, additionally the continuous competition for land with the sugarcane agribusiness system, have led the so-called "citrus belt" moving increasingly towards the southern state of São Paulo. This situation has led to increased costs and reducing the productivity and efficiency throughout the whole chain. The Brazilian citrus industry should search for urgent solutions, which cannot only bring longevity to the business, but also as a more critical issue: their own survival. Thus, this study aims to verify whether the gradual introduction of new varieties of orange and the development of a model of integrated planning within the technical of system dynamics can contribute to improve the performance and the competitiveness of this agribusiness system. The research method used was deductive hypothetical with the necessary information was gathered through semi-structured questionnaires and personal interviews with agents in the sector. The model was applied to the part of the citrus production chain, which covers the members of agricultural production and industrial processing. The results of the developed model showed that there are significant potential gains in performance, reflected in the increased EBITDA margin on the industrial processing side and in the net income per hectare and the price of the orange box on the agricultural production side, if they established together an integrated planning of production, crop-season to crop-season.